Public Capital and Output Growth in Portugal : An Empirical Analysis - Ligthart, Jenny (IMF Working Papers; Working Paper, 2000)
The paper investigates the growth effects of public capital in Portugal using annual data for the period 1965-95. Both a production function and a vector autoregressive model are estimated. Public capital is shown to be a significant long-term determinant of output growth. The size of the estimated production elasticity indicates, in line with studies for other countries, a substantial growth payoff from public investment. Disaggregating public capital shows that investment related to, among other things, roads, railways, and airports is more productive than public investment in other major categories.